Simultaneous Determination of Halobetasol and Salicylic Acid Related Substances by Reversed Phase High Performance Liquid Chromatographic Method - Ankam, R.; Mukkanti, K.; Durgaprasad, S.; Naidu, P.V.L. (Asian Journal of Chemistry, 2010)
A simple fast, accurate, precise and cost effective reverse phase high performance liquid chromatographic method is developed for simultaneous determination of halobetasol propionate and salicylic acid impurities in the ointment formulation. The chromatography equipped with inertsil C-8 (250 mm × 4.6 mm) column using a mobile phase of buffer (0.1 % of orthophosphoric acid) and acetonitrile with a flow rate of 1.5 mL/min, with ultraviolet detector configured at 231 nm. The method is found to be linear in the range of 0.118-17.734 μg/mL for 4-hydroxy benzoic acid, 0.120-9.036 μg/mL for 4-hydroxy isophthalic acid, 0.12-3.586 μg/mL for phenol, 0.103-8.987 μg/mL for salicylic acid, 0.069-1.480 μg/mL for diflorasone 21 propionate, 0.071- 1.472 μg/mL for diflorasone 17 propi-onate 21 mesylate and 0.057-1.514 μg/mL for halobetasol propionate.